Addiction Biomarkers: Dimensional Approaches to Understanding Addiction. Issue 2 (February 2018) - Kwako, Laura E.; Bickel, Warren K.; Goldman, David
Abstract : Trends towards dimensional approaches in understanding psychiatric disorders may also be applied to addictive disorders. Advances in our understanding of the neurobiology of addiction can inform these efforts. Furthermore, dimensional approaches to addiction, such as the proposed Addictions Neuroclinical Assessment (ANA), may be used in identifying novel addiction biomarkers, and refining ones that currently exist. These biomarkers, derived from both an understanding of the neurobiology of addiction and behavioral phenotypes, represent a departure from traditional markers of alcohol-relevant biomarkers, such as tests of liver function (LFTs). We posit that a potential addiction-relevant biomarker is reinforcer pathology, found to be relevant across addictions to different substances, and which may offer a target for modification through the use of episodic future thinking. Highlights: To better understand addiction, support is growing to undertake dimensional approaches that are based on neuroscience. Neuroscience-based dimensional approaches may be used to identify and refine candidate biomarkers of addictive disorders. Empirical evidence suggests that reinforcer pathology can be used as a biomarker of addictive disorders.